Glimpses Of Dynamic Biodiesel Product Pricing Model - Hussain, Zakir; Meghavathu, Deepa; Kumar, Rakesh (International Journal of Engineering and Technology, 2018)
Entrepreneurship development, energy crisis, rising fossil fuel prices, increasing greenhouse gas emission and waste management are the key issues which concern the government to tackle them sustainably. The advent of biodiesel as a fuel paves the pathway to handle these issues and together it creates an opportunity to develop a small/medium to large-scale biodiesel production units. Current research is mainly focused on creating the roadmap to solve the feedstock scarcity issue faced by Indian biodiesel industries through the field survey. It also presents a robust model framework to fix the minimum selling price of biodiesel through energy input-output and cost input-out analysis in producing a unit volume of biodiesel. The results show that the surveyed area may have the potential to supply on an average of 129 liters/day waste vegetable oil. Energy analysis shows that the highest share of energy 71.84% was from waste vegetable oil followed by 25.99% corresponds to alcohol. Others are being at 0.85% due to the catalyst, 0.44% due to electricity, 0.68% due to machinery and 0.2% due to human labor. Cost analysis shows that the highest share of cost 52.13% was due to alcohol followed by 39.34% due to waste cooking oil.Â